Analisis Faktor-Faktor Yang Memengaruhi Niat Penggunaan Berkelanjutan E-Wallet - Ariel, Jonathan; Iriyanti, Ira (Jurnal Manajemen dan Usahawan Indonesia, 2023)
The development of technology led to a series of disruptions that replaced conventional financial systems. The emergence of COVID-19 pandemic accelerated the adoption of digital financial services, one of which is e-wallet. With pandemic over, e-wallet companies must be able to retain their users and made sure they continue to use e-wallet for transaction. Hence, this research aims to understand the factors determining user’s intention to continue using e-wallet as their payment method. This research applies Technology Continuation Theory with the extension of Trust, Habit, Price Benefit, and Operational Constraints. This research gathered data from 251 respondents who lives on the island of Java. Data processing was conducted using the SEM-PLS Method. Research findings indicate that Habit, Attitude, and Satisfaction has a positive and significant influence on the Intention To Continue Using E-wallet, whilst Operational Constraints have a negative and significant influence. For e-wallet providers, this research provides a deeper understanding of the factors when considering continued usage of e-wallet and can potentially be used during decision making process regarding the development of e-wallet products.